Pulmonary involvement in patients with hematological malignancies - Azoulay, Elie (Springer, 2011)
The number of patients treated for hematological malignancies is increasing steadily. To obtain the highest possible cure rates, aggressive treatments have been introduced, including high-dose chemotherapy, stem cell transplantation, and targeted therapies. As a result, overall and disease-free survival rates have improved substantially; however, this has been achieved at the price of life-threatening toxic and infectious complications that chiefly target the lung. This book provides clinicians caring for patients with hematological malignancies with detailed, up-to-date information on all relevant aspects of pulmonary involvement. Individual sections are devoted to epidemiology, diagnostic strategy, lung infections, non-infectious pulmonary involvement, and treatment, including decision making in patients with acute respiratory failure. Each of these sections contains a number of chapters, all written by leading international experts. In addition, the reader?s attention is drawn to important "pearls" relating to each condition.